Study on the Movements of Organometallic Halide Perovskite Crystals on their Films. Issue 47 (17th December 2019) - Song, Tingyu; Bi, Huan; Wei, Qi; Yan, Su; Wang, Shiwei
Abstract: Recently, organometallic halide perovskites (OMHPs) have attracted significant attention due to their high light absorption coefficient, high charge carrier mobility, and long carrier lifetime. One of the key shortcomings of the OMHP device application is its poor stability under humid conditions. Thus, it is important to study the relationship between humidity and OMHP crystals in their thin films. In this work, the large‐scale movement behavior of CH3 NH3 PbI3‐x Clx crystals in their films is discovered. It is concluded that the number of moving CH3 NH3 PbI3‐x Clx crystals can be controlled by the humidity of the external environment. The movement behavior of the perovskite grains is attributed to the asymmetric decomposition of perovskite under high relative humidity (RH) conditions. Abstract : CH3 NH3 PbI3‐x Clx perovskite grains can move under high relative humidity conditions. In addition, the number of moving grains increases with increasing relative humidity. This novel phenomenon is caused by the asymmetric decomposition of the grains, and it is powered by the electrolyte gradient under the humidity conditions of the external environment.